Genome-wide mosaicism within Mycobacterium abscessus: evolutionary and epidemiological implications. (December 2016) - Sapriel, Guillaume; Konjek, Julie; Orgeur, Mickael; Bouri, Laurent; Frézal, Lise; Roux, Anne-Laure; Dumas, Emilie; Brosch, Roland; Bouchier, Christiane; Brisse, Sylvain; Vandenbogaert, Mathias; Thiberge, Jean-Michel; et al.
Abstract Background In mycobacteria, conjugation differs from the canonical Hfr model, but is still poorly understood. Here, we quantified this evolutionary processe in a natural mycobacterial population, taking advantage of a large clinical strain collection of the emerging pathogenMycobacterium abscessus (MAB). Results Multilocus sequence typing confirmed the existence of threeM. abscessus subspecies, and unravelled extensive allelic exchange between them. Furthermore, an asymmetrical gene flow occurring between these main lineages was detected, resulting in highly admixed strains. Intriguingly, these mosaic strains were significantly associated with cystic fibrosis patients with lung infections or chronic colonization. Genome sequencing of those hybrid strains confirmed that half of their genomic content was remodelled in large genomic blocks, leading to original tri-modal 'patchwork' architecture. One of these hybrid strains acquired a locus conferring inducible macrolide resistance, and a large genomic insertion from a slowly growing pathogenic mycobacteria, suggesting an adaptive gene transfer. This atypical genomic architecture of the highly recombinogenic strains is consistent with the distributive conjugal transfer (DCT) observed inM. smegmatis . Intriguingly, no known DCT function was found inM. abscessus chromosome, however, a p-RAW-like genetic element was detected in one of the highly admixed strains. Conclusion Taken together, our results strongly suggest that MAB evolution is sporadically punctuated by dramatic genome wide remodelling events. These findings might have far reaching epidemiological consequences for emerging mycobacterial pathogens survey in the context of increasing numbers of rapidly growing mycobacteria andM. tuberculosis co-infections.